Maternal exposure to Bonny Light Crude Oil Altered Reproductive indices in Male and Female offspring of Wistar rats (Nigerian Journal of Physiological Sciences, 2021)
In this study, the effects of maternal exposure to Bonny Light Crude Oil (BLCO) on reproductive functions of the offspring was investigated in Wistar rats. Ten pregnant rats were divided into two groups (n=5). Group 1 served as the control, it was administered 0.75ml/Kg bwt/day normal saline and Group 2 was administered 0.75ml/Kg bwt/day BLCO. Serum hormonal profile, sperm indices, estrous cycle length and pubertal timing were assessed as measures of reproductive function. Tissue Malondialdehyde, Catalase and SOD activities were assessed as indices of oxidative stress. Results obtained showed that BLCO significantly (p